Exploring Mother-in-Law and Daughter-in-Law Conflicts in Contemporary Family Structures - Annisa, Qori; Ahmad, Amala Bilqis; Al-Faidah, Ashimatul Wahdah (USRATY : Journal of Islamic Family Law, 2024)
Conflicts between mothers-in-law and daughters-in-law are common phenomena in family dynamics, especially within the context of increasingly diverse and complex contemporary family structures. This study aims to explore the factors influencing conflicts between mothers-in-law and daughters-in-law and how such conflicts can be managed in family relationships today. Using a qualitative approach, this research gathers data through in-depth interviews and observations of families experiencing conflicts in mother-in-law and daughter-in-law relationships. The findings show that various factors, such as differences in values and expectations between mothers-in-law and daughters-in-law, gender roles still influenced by traditional norms, as well as social and economic pressures, play a significant role in triggering conflicts. Furthermore, ineffective communication and a lack of understanding of each other’s roles within the family also contribute to exacerbating the situation. The study also found that there are differences in how mothers-in-law and daughters-in-law handle conflicts, depending on their educational background, culture, and age. To address these conflicts, it is important to build open communication and mutual understanding, as well as prioritize empathy among family members. This study suggests the need for a more inclusive and socially sensitive approach in order to create harmonious relationships between mothers-in-law and daughters-in-law, and emphasizes the importance of family education that can help manage intergenerational conflicts in the modern era.